2013
DOI: 10.1097/sla.0b013e31828d4b76
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair Versus Open Repair of Ruptured Abdominal Aortic Aneurysms

Abstract: This trial did not show a significant difference in combined death and severe complications between EVAR and OR. Mortality for OR both in randomized patients and in cohort patients was lower than anticipated, which may be explained by optimization of logistics, preoperative CT imaging, and centralization of care in centers of expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(108 citation statements)
references
References 26 publications
2
100
1
5
Order By: Relevance
“…The timing of death was assessed from randomisation (for the IMPROVE trial) and from hospital admission (for the AJAX 19 and ECAR 22 trials). Logistic regression analysis was used to estimate the OR of both 30-and 90-day mortality for endovascular repair (or endovascular strategy) compared with open repair, adjusting for trial to obtain a one-stage fixed-effect pooled estimate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The timing of death was assessed from randomisation (for the IMPROVE trial) and from hospital admission (for the AJAX 19 and ECAR 22 trials). Logistic regression analysis was used to estimate the OR of both 30-and 90-day mortality for endovascular repair (or endovascular strategy) compared with open repair, adjusting for trial to obtain a one-stage fixed-effect pooled estimate.…”
Section: Discussionmentioning
confidence: 99%
“…8. Conduct an individual patient meta-analysis of participants randomised in all of the European randomised trials [Amsterdam Acute Aneurysm trial (AJAX), 19 Endovasculaire versus Chirurgie dans les Anévrysmes Rompus (ECAR) 22 and IMPROVE 23 ], with respect to common 30-day and 1-year outcomes. 9.…”
Section: Objectives Of the Improve Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…Three randomised trials including a total of 761 patients were identifi ed, with 388 patients randomised for EVAR and 373 patients with open surgical repair. While Hinchliff e et al [3] focused only on 30-day outcomes, the AJAX [4] and IMPROVE [5] trials also aimed at longer outcomes, although no long-term data from IMPROVE have been published to date. In summary, there was no diff erence regarding in-hospital or 30-day mortality between EVAR and surgery (OR 0.91, 95 % CI 0.67 to 1.22), as well as for in-hospital stroke (OR 0.71, 95 % CI 0.12 to 4.31) and cardiac complications (OR 1.12, 95 % CI 0.38 to 3.30).…”
Section: Evar In Ruptured Abdominal Aneurysmsmentioning
confidence: 99%
“…Acute re-operation rate was also not diff erent between the two approaches (OR 0.89, 95 % CI 0.39 to 2.01). The AJAX trial [4] was the only study which evaluated spinal cord ischaemia and found no diff erences (OR 3.16, 95 % CI 0.13 -79.17). The IMPROVE trial [5] (performed in the United Kingdom) assessed costs at 30 days but did not fi nd a signifi cant diff erence (13,433 GBP after EVAR compared to 14,619 GBP after open repair).…”
Section: Evar In Ruptured Abdominal Aneurysmsmentioning
confidence: 99%